Alectinib combined with VRCD and BV monoclonal antibody for the treatment of ALK-positive large B-cell lymphoma: a case report and literature review - Wang, Hongxia; Bai, Junjun; Zhang, Bei; Pei, Zhixin; Zhao, Yingxin; Gu, Jingjing; Fang, Zhiyu; Liu, Miaomiao; Liang, Xun; Song, Qinglin (Frontiers in Oncology, 2025)
We report a case of a 53-year-old male patient who was diagnosed with anaplastic lymphoma kinase-positive large B-cell lymphoma. A pathological examination showed plasma-cell immunophenotype negative for mature B-lymphocyte markers. The patient received three cycles of an “alectinib + Vincristine + Rituximab + Cyclophosphamide + Doxorubicin (VRCD) “ regimen. In the fourth cycle, brentuximab vedotin monoclonal antibody treatment was added to increase the efficacy of the treatment. Positron emission tomography-computed tomography and a bone marrow examination were carried out after four cycles, revealing a complete response. Stem cells were successfully harvested. Thus far, the patient has undergone six treatment cycles and successfully received autologous hematopoietic stem cell transplantation. Currently, the patient is receiving maintenance therapy with alectinib and lenalidomide and remains in a favorable clinical condition.